Physical environment of learning as the third educator - Adlerstein Grimberg, Cynthia (Base Diseño e Innovación, 2016)
The idea of designing new furniture for early childhood education was born after the study on anthropometric table information about child population in Chile, conducted by Jimena Rojas—at that time academic at the Design School UC—in conjunction with JUNJI. The foregoing, since there were no studies with local results and the only references available were European or American figures.